KERABAT LAUT: Studi Teologi Kontekstual Mitos Eno Karang di Aru - Natalya Leviana Papasoka; Jafet G Damamain (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2019)
In this paper, researchers would explain about the folklore of Eno Karang at indigenous community of Aru with Strauss’ structuralism as our theoretical approach. We would construct the values which can be adopted from that folklore, and also about the interconnection between Aru community and their ocean. Thus, researchers construct contextually theological notions based on the story of Eno Karang. After conducting this research, one interesting thing that has been found is that the story of Eno Karang is one of the myths in Aru which basically is talked about the siblinghood relation between human and the ocean. Aru people are the sibling of the ocean because under the ocean, their ancestors live in the physical form of ocean biodiversity. Because of this relationship, the violation against the ocean is totally prohibited. Based on that relationship, they assume that the ocean will be their judge or punisher, so they must maintain a harmonious life with the ocean as an equal creature in the siblinghood consciousness.